Antihypertensive Treatment is associated with MRI-Derived Markers of Neurodegeneration and Impaired Cognition: A Propensity-Weighted Cohort Study. - Edwards, Jodi D; Ramirez, Joel; Callahan, Brandy L; Tobe, Sheldon W; Oh, Paul; Berezuk, Courtney; Lanctôt, Krista; Swardfager, Walter; Nestor, Sean; Kiss, Alexander; Strother, Stephen; Black, Sandra E (J Alzheimers Dis, 2017)
BACKGROUND: Hypertension is an important risk factor for Alzheimer's disease (AD) and cerebral small vessel disease. Angiotensin converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are common anti-hypertensive treatments, but have differential effects on cortical amyloid. OBJECTIVE: The objective of this study was to evaluate associations between anti-hypertensive treatment, brain volume, and cognition, using a propensity-weighted analysis to account for confounding by indication. METHODS: We identified a cohort of normal elderly adults and individuals with mild cognitive impairment (MCI) or AD (N = 886; mean age = 75.0) from the Alzheimer's Disease Neuroimaging Initiative. Primary outcomes were brain parenchymal fraction, total hippocampal volume, and white matter hyperintensity (WMH) volume. Secondary outcomes were standardized scores on neuropsychological tests. Propensity-weighted adjusted multivariate linear regression was used to estimate associations between anti-hypertensive treatment class and MRI volumes and cognition. RESULTS: Individuals treated with ARBs showed larger hippocampal volumes (R2 = 0.83, p = 0.05) and brain parenchymal fraction (R2 = 0.83, p = 0.01) than those treated with ACEIs. When stratified by diagnosis, this effect remained only in normal elderly adults and MCI patients, and a significant association between ARBs and lower WMH volume (R2 = 0.83, p = 0.03) emerged for AD patients only. ARBs were also associated with significantly better performance on tests of episodic and verbal memory, language, and executive function (all p < 0.05). CONCLUSIONS: Findings are consistent with evidence for a neuroprotective effect of treatment with ARBs for brain structure and cognition. This study has potential implications for the treatment of hypertension, particularly in elderly adults at risk of cognitive decline and AD.

Functional Reserve: Experience Participating in Instrumental Activities of Daily Living is Associated with Gender and Functional Independence in Mild Cognitive Impairment. - Berezuk, Courtney; Zakzanis, Konstantine K; Ramirez, Joel; Ruocco, Anthony C; Edwards, Jodi D; Callahan, Brandy L; Black, Sandra E (J Alzheimers Dis, 2017)
BACKGROUND: Gender differences in instrumental activities of daily living (IADLs) in mild cognitive impairment (MCI) and Alzheimer's disease may be explained by gender differences in IADL involvement. OBJECTIVE: We introduce a novel theoretical construct, termed functional reserve, and empirically examine gender differences in IADL experience as a proxy of this reserve. METHODS: We cross-sectionally examined men (n = 502) and women (n = 340) with MCI from the Alzheimer's Disease Neuroimaging Initiative (ADNI). Demographic factors, depressive symptoms, neuropsychological scores, and IADL experience were included as independent variables and total Functional Activities Questionnaire (FAQ) scores as the dependent variable. Regression analyses were performed on the full cohort and stratified by gender to identify differential predictive relationships for men and women. RESULTS: Gender was associated with total FAQ (p < 0.05) until adjusting for IADL experience. Furthermore, the combination of cognitive measures accounted for the most variance in functional dependence (12% explained, p < 0.001), although IADL experience was the most important single variable (4.8% explained, p < 0.001). Stratification by gender revealed that IADL experience accounted for 6.6% of the variance in FAQ score in men (p < 0.001) but only 2.4% in women (p = 0.001); however, the interaction between gender and experience was not statistically significant. DISCUSSION: A small effect of men showing greater functional dependence in MCI may be explained by lower IADL experience. Additionally, IADL experience was associated with superior functioning in all analyses, potentially through increased functional reserve. This concept of functional reserve may have implications for identifying individuals at risk for IADL dependence, preventing or delaying decline, and potentially treating functional impairment.